VD_FINDINFO HC / 2012 / 28 vom 18. November 2011 - VD Tribunal cantonal (2011)
EXPERTISE, PREUVE À FUTUR, LITISPENDANCE, COMPÉTENCE | 29 al. 2 Cst., 158 al. 1 CPC (CH), 320 let. b CPC (CH), 62 CPC (CH)